IMMU-12. IL13Ra2-CAR T CELLS STIMULATE ENDOGENOUS IMMUNE RESPONSES AGAINST MURINE GLIOBLASTOMAS. (11th November 2019) - Alizadeh, Darya; Wong, Robyn; Pecoraro, Joseph; Yang, Xin; Forman, Stephen; Brown, Christine E
Abstract: Malignant gliomas (MG) are one of the deadliest cancers with very limited therapeutic options. Chimeric antigen receptor (CAR)-T cell therapy has emerged as a powerful strategy for B-cell malignancies and may offer new opportunities to improve outcomes for patients with MGs. Our team is clinically evaluating IL13Rα2-targeted CAR-T cells for the treatment of recurrent IL13Rα2-positive MGs [NCT02208362]. While this trial is ongoing, we have previously reported that one patient with recurrent multifocal glioblastoma achieved a complete response post-IL13Rα2-CAR-T therapy despite the non-uniform expression of IL13Rα2 on the tumor. The therapeutic response against IL13Rα2-negative cells suggests CAR-T cells may stimulate endogenous immune responses. To study the interplay between CAR-T cells and host immune subsets, we have established a syngeneic immunocompetent glioma model, which recapitulates the tumor microenvironment (TME) of patients. Murine IL13Rα2-CAR-T cells mediate potent antitumor activity against IL13Rα2-engineered KR158, a highly invasive murine glioma model. Interestingly, mice "cured" from CAR-T therapy, after rechallenge, can successfully reject the tumors. Furthermore, we demonstrate comparable response rate in mice bearing gliomas with mixed antigen expression (50%IL13Rα2+/50%IL13Rα2-) vs 100% IL13Rα2+. Characterization of the TME post-CAR-T therapy indicates activation of endogenous cytotoxic CD8 T and myeloid cells, and decrease in the frequency of T regulatory cells. Further analyses reveal that tumor-associated macrophages (TAMs) may be reprogrammed during CAR-T therapy to exhibit tumoricidal activity and may promote the activation of endogenous T cells (CD4/CD8 T cells) resulting in enhanced antitumor activity. Current studies are focusing on the characterization of host immune cells to identify the mechanisms involved in induction of host immune responses mediated by CAR-T cell therapy. Our data thus strongly suggest that CAR-T therapy has the potential to reshape the glioma microenvironment creating a context permissible to elicit effective endogenous antitumor immunity.